The hunter : a graphic novel - Cooke, Darwyn (Cooke, Darwyn. Richard Stark's Parker, 2009)
Parker, a master thief, comes to New York City bent on getting revenge both on the woman who betrayed him and on the former partners who double-crossed him and cheated him of his money.